BETTER WITH OZONE, OR NOT? AN IN-VIVO STUDY OF OZONE THERAPY AS A PRE-TREATMENT BEFORE FISSURE SEALANT APPLICATION. - Merve Aksoy; Firdevs Tulga Öz; Murat Çetinkaya (Cumhuriyet University, 2020)
Objectives: The aim of the study was to evaluate clinical achievements of ClinproTMSealant and Teeth mate F-1 fissure sealants with or without ozone treatment as well as retention, marginal discoloration, marginal adaptation and caries formation under in-vivo conditions. Materials and Methods: The study was carried out on 166 patients whose ages differs between 9-12 and 3 different groups were formed above them according to split mouth technique, in order to evaluate clinical achievements of fissure sealants with or without ozone treatment. Group 1: ClinproTMSealant and Teethmate F-1 were applied on a total of 104 first lower permanent molar teeth which were randomly selected from 52 patients. Group 2: ClinproTM Sealant and ClinproTM Sealant following ozone treatment were applied on 112 randomly selected teeth of 56 patients. Group 3: Teeth mate F-1 and Teeth mate F-1 following the ozone treatment were applied on 116 first lower permanent molar teeth which were randomly selected from 58 patients. Based on the modified USPHS criteria, the impacts on general achievement, retention, marginal fit, marginal discoloration and caries formation on occlusal surfaces were evaluated in 3rd,6th,12th,18th months. Chi-Square Test and Fisher's Exact Test were used for analyses of the data. Results: In Group 1; Clinpro™Sealant showed higher clinical success rates in all observation periods. Considering marginal adaptation and retention, Clinpro™Sealant group was statistically significantly different in 18th month observations. In group 2 and group 3, there was not statistically significantly difference (p>0.05) between control and experimental groups but clinical success rates of Clinpro ™ Sealant and Teetmate F-1 with Ozone Treatment were higher than the same groups without ozone pretreatment during all observation periods. Conclusion: It was determined that, ClinproTMSealant yielded more successful results than the Teethmate F-1 under in-vivo conditions. Although there wasn't any statistically significantly difference between Group 2 and Group 3 in which Ozone as a pretreatment method before performing fissure sealant was considered, the Ozone pretreatment method's success rates were higher clinically according to Bravo, Alpha and Charlie Scores. It seems that performing Ozone Therapy before applying fissure sealant is a successful method for preventing pit and fissure sealants, clinically.